Primary pulmonary Ewing's sarcoma: rare cause of massive hemothorax in a young girl-case report - Xuefeng Ling; Jianlin Tong; Liangliang Wang; Chuan Yao; Zhiying Chen (BMC, 2021)
Abstract Background Ewing's sarcoma is a common malignant bone tumor in children and young adults. Rarely, extra-skeletal soft tissues and visceral organs can also be the site of origin of Ewing's sarcoma. Primary pulmonary Ewing's sarcoma is an extremely rare malignancy. Case presentation We report an unusual case of primary pulmonary Ewing's sarcoma in a 15-year-old girl who initially presented with massive hemothorax. By histopathology evaluation of surgical biopsy specimens, the diagnosis of extraosseous Ewing's sarcoma was confirmed by both light microscopy and immunohistochemistry. Emergency, open surgery was performed by thoracic surgery at an early stage. After 3 cycles of chemotherapy, the patient was found to be stable at follow-up examination. No more hydrothorax or other symptoms. Conclusions We have described an extremely rare case of primary pulmonary Ewing's sarcoma with massive hemothorax. The patient underwent surgical resection and postoperative chemotherapy, no sign of recurrence to date as an outcome.